Teknik eğitim ve eğitim fakültesi öğrencilerinin ilk ve ortaöğretim ile yükseköğretimdeki mesleki benlik algılarının karşılaştırılması - (:unkn) unknown (My University, 2009)
Araştırmanın amacı; teknik eğitim ve eğitim fakültelerindeki öğretmen adaylarının ilgi ve yeteneklerine ilişkin kendilerini geçmişte ve bugün nasıl algıladıklarının, bu algılar ve bölümler arasında farklılığın olup olmadığının belirlenmesidir. Araştırma, betimsel bir çalışma olup, ilişkisel tarama modeli ile yürütülmüştür. Araştırmanın evrenini Marmara Üniversitesi Atatürk Eğitim Fakültesi ve Teknik Eğitim Fakültesi, örneklemini ise bu fakültelerde yer alan bölümlerden tesadüfî örnekleme yöntemi ile seçilmiş 346 öğretmen adayı oluşturmaktadır. Araştırmaya veri toplamak amacıyla araştırmacılar tarafından geliştirilen ve alan uzmanları tarafından kontrol edilerek düzeltilen 44 soruluk anket, “İlköğretimde Yöneltme Yönergesi”nde yer alan “Öğrenci Gözlem Formu”nun gözlem ölçütlerinden yararlanılarak geliştirilmiştir. Ankette yer alan 44 sorudan; 1-7. sorular; “sözel-dilsel ilgi ve yetenekler”, 8-13. sorular; “şekil-uzay ilgi ve yetenekler”, 14-18. sorular; “mekanik ilgi ve yetenekler”, 19-23. sorular; “sayısal ilgi ve yetenekler”, 24-33. sorular; “sanat-spor ilgi ve yetenekler”, 34-44. sorular; “kişilik özellikleri” konusunda öğrencinin “geçmişte” ve “şimdi” olarak iki ayrı boyutta ele alınan ifadeleri içermektedir. Araştırma sonucunda elde edilen puanların dağılımlarının normal dağılım eğrisine uygunluğunun test edilmesi amacıyla her bir alt boyut için Kolmogorov-Simirnov testi yapılmış ve elde edilen değerlerde dağılımın normal olduğu belirlenmiştir. Bu nedenle elde edilen veriler 0.05 anlamlılık düzeyinde eşleştirilmiş iki grup ve ilişkisiz grup t-testleri ile analiz edilmiştir. Elde edilen bulgularda araştırmaya katılan öğrencilerin; tüm alanlara ilişkin şimdiki farkındalıklarının geçmiştekinden daha fazla olduğu ve eğitim fakültesi öğrencilerinin teknik eğitim fakültesi öğrencilerine göre şimdiki ilgi ve yetenek alanlarındaki algılarının daha yüksek olduğu sonuçlarına ulaşılmıştır. Araştırmanın son bölümünde elde edilen sonuçlar doğrultusunda yararlı olacağı umulan öneriler getirilmeye çalışılmıştır.

The purpose of this research, is to determine the perception of the teacher candidates studying in the technical education and education faculties of themselves in the past and today regarding their interests and abilities and the possible differences between these perceptions if there is any. This research which is a descriptive study was carried out with a relational screening model. The universe of the research is restricted to Atatürk Faculty of Education and Faculty of Technical Education in Marmara University and the population of the study consists of 346 teacher candidates selected with random sampling among the departments of these faculties. In order to gather data for this study, a questionnaire of 44 questions which was developed by the researchers and corrected by field experts, was developed based on the “Student Observation Form” in the “Governing Regulations on Orientation in Primary Education”. Among 44 questions, questions 1-7 cover “verbal-linguistic interests and abilities”, questions 8-13 cover “shape-spatial interests and abilities”, questions 14-18 cover “mechanical interests and abilities”, questions 19-23 cover “numerical interests and abilities”, questions 24-33 cover artistic-sportive interests and abilities”, questions 34-44 cover “personal traits” of the students expressed in two dimensions as “in the past” and “in the present”. In order to determine the conformity of the data obtained as a result of the research with the normal distribution curve, Kolmogorov-Simirnov test was used for each sub-dimension and it is determined that the distribution is normal. Therefore, the data obtained was analyzed with t-tests of 0.05 significance level. As a result, it was determined that the current awareness of the students related to all fields is more than in the past. In addition, the current perception of the students in the faculty of education related to the fields of interest and ability was determined to be higher than the perception of the students in the faculty of technical education. In the final part of the research, some recommendations are presented in accordance with the results of the study.
The comparison of occupational self-perception during primary, secondary and high education of the students in the technical education faculty with those in the education faculty